Use of Wood Resources in Central Argentina: A multivariate approach for the study of phytogeography and culture - Rodríguez López, Santiago; Arias Toledo, Bárbara; Galetto, Leonardo (Ethnobotany Research and Applications, 2015)
Changes in land use and forest loss determine not only the loss of biodiversity, but the associated traditional ecological knowledge. Thus, knowing the several uses of forest resources by rural communities might help in guiding conservation efforts. We applied a multivariate approach to evaluate knowledge on uses of wood species—based on environmental factors and participants’ (N = 114) socioeconomic characteristics—in six rural communities of Córdoba Province, Argentina, located in three different phytogeographical areas. Older men with unstable jobs and low education represent the embodiment of those who know about wood resources. Although the multivariate analysis suggests that socioeconomic factors are important when determining the known uses of wood resources within each area, environmental factors such as the availability of species considerably contribute to the characterization of the different communities. Quantitative analysis, including the socioeconomic characterization of human populations, might provide a valuable tool when planning policies for management and conservation of fuelwood resources.